Pulsed current wave shaping with a transmission line by utilizing superposition of a forward and a backward voltage wave for fast capillary Z-pinch discharge - Sakai, Y.; Takahashi, S.; Watanabe, M.; Kim, G.-H.; Hotta, E. (Review of scientific instruments, 2010)
By using a water transmission line, current wave shaping was demonstrated for a fast capillary Z-pinch discharge recombination soft x-ray laser study. The pulsed power system consists of a water capacitor, a gap switch, a transmission line, and a capillary plasma load. A voltage wave initiated at the water capacitor propagates toward the capillary load through the transmission line. Control of the pulse delay that occurred in the transmission line provides the superposition of the forward and the backward voltage waves effectively in order to perform current wave shaping with higher current amplitude and rapid current decay.